Potential of Aedes albopictus to cause the emergence of arboviruses in Morocco - Amraoui, Fadila; Ben Ayed, Wiem; Madec, Yoann; Faraj, Chafika; Himmi, Oumnia; Btissam, Ameur; Sarih, Mhammed; Failloux, Anna-Bella (PLOS Neglected Tropical Diseases, 2019)
Author summary The Asian tiger mosquito Aedes albopictus is responsible for the transmission of several arboviruses such as dengue and chikungunya viruses. In 30 to 40 years, it has extended its geographical distribution in both tropical and temperate regions of all continents. The species was first detected in September 2015, in Rabat, Morocco. Using experimental infections, we demonstrated that Ae. albopictus Morocco are competent to transmit zika and yellow fever viruses in addition to the transmission of dengue and chikungunya viruses. Our results are central to suggest developing the most effective national surveillance program and to designing the most suitable control strategy to avoid the mosquito spreading beyond its point of entry in Morocco.